The formation of added value in the marketing chain of the meat processing industry product promotion - Рудь, Віта Вікторівна (Technology audit and production reserves, 2015)
The existing problems of formation of added value are analyzed in the article. Three main stages of promotion of meat products from agricultural producer to the final consumer are proposed: production, processing and trading. The production stage of formation of added value implies that the main subject of its creation is an agricultural manufacturer. This stage is based on the most responsible process - production of feed, feeding and livestock as well as its slaughter (if any slaughterhouse). In some cases (mostly farmers and small farms) sell cattle through intermediaries (purveyors). However, the cost of manufacturing stage of formation of added value is largest and most significant in comparison with other stages that forming added value. Processing stage of formation of added value involves its creation in processing for meat or raw meat realization (processed or packaged). This stage of formation added value is the main because it provides the most cost that must calculate that the company was profitable. The cost of trading stage of formation of added value provided only on sales and expenses that do not concern the product itself, but concern its sales. The wholesale companies, that are represented as independent wholesale companies and trading houses meat processing plants, includes in the chain for sales of processed meat. The wholesale companies sell sausages and chilled and frozen convenience food. It is proposed a functional-block diagram of formation of added value and method of calculating the added value at each of the suggested steps.